2020
DOI: 10.18332/tpc/127375
|View full text |Cite
|
Sign up to set email alerts
|

Tobacco use patterns and predictors among college students in Mangalore, South India: Findings from the Global Adult Tobacco Survey

Abstract: INTRODUCTION Tobacco use is a leading cause of death and disability worldwide, particularly in SouthEast Asia. The tobacco problem in India is probably more complex than in any other country, with a huge consequential burden of tobacco related diseases and deaths. The present study aimed at analyzing the pattern and predictors of tobacco use among college students aged 18-24 years, using the Global Tobacco Surveillance System (GTSS). METHODS A cross-sectional study was conducted among 2063 students, from 30 co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…This study was found that students living in hall were more likely to smoke than those living elsewhere, while another study found that smoking prevalence is higher among students living away from home 19 . Additionally, smoking prevalence is comparatively higher among students from urban areas than among those from rural areas 23 . These results indicate that when students live away from home or away from their parents, they have a higher chance of being smokers.…”
Section: Discussionmentioning
confidence: 95%
“…This study was found that students living in hall were more likely to smoke than those living elsewhere, while another study found that smoking prevalence is higher among students living away from home 19 . Additionally, smoking prevalence is comparatively higher among students from urban areas than among those from rural areas 23 . These results indicate that when students live away from home or away from their parents, they have a higher chance of being smokers.…”
Section: Discussionmentioning
confidence: 95%
“…[3][4][5][6][7][8][9][10] Prevalences between 4.8% and 43.6% have been reported in universities in other countries (Figure 1). 16,[18][19][20][21] The prevalence of smoking among university students in Turkey has decreased over the years. However, in this research we conducted after the COVID-19 pandemic, we found an increase in prevalence compared to previous studies.…”
Section: Discussionmentioning
confidence: 99%
“…20 But no significant difference has been observed in terms of tobacco use between male and female university students in the USA. 18 Tobacco use is being regarded as a male behavior represents the basic reason for this variation. Older research from Turkey reported wide differences in prevalence values between men and women, while the difference has diminished in more recent research.…”
Section: Figure 1 Prevalences Of Cigarette Smoking Among University S...mentioning
confidence: 99%
See 1 more Smart Citation
“…Using tobacco and alcohol could be considered symbolic of adulthood. In addition, early exposure and initiation, curiosity, peer influence and pressure, the industry's advertisement and promotional strategies to target youth, 39,40 easy availability, and SU within the household may provide an impetus for students to use substances. 41 Further, students' parents' occupations and income were seen to be associated with SU.…”
Section: Discussionmentioning
confidence: 99%